High-Efficiency Grating Coupler in 400 nm and 500 nm PECVD Silicon Nitride With Bottom Reflector - Siddharth Nambiar; Abhai Kumar; Rakshitha Kallega; Praveen Ranganath; Shankar Kumar Selvaraja (IEEE Photonics Journal)
We design and experimentally demonstrate highly efficient Silicon Nitride based grating couplers with bottom distributed Bragg reflectors. All the layers were deposited using plasma enhanced chemical vapor deposition processing. We present gratings on two Silicon Nitride thickness (400 nm and 500 nm) platforms. On a 500 nm thick Silicon Nitride, we show a peak coupling efficiency of $-$ 2.29 dB/coupler at a wavelength of 1573 nm with a 1 dB bandwidth of 49 nm. On a 400 nm thick platform, we demonstrate a coupling efficiency of $-$ 2.58 dB/coupler at 1576 nm with a 1 dB bandwidth of 52 nm. The demonstrated coupling efficiency is the best reported as yet, for both 400 nm and 500 nm thick, plasma deposited Silicon Nitride platforms.